(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
Traditions of wayang puppetry in Indonesia realize what Philippe Descola refers to as an «animist ontology». Not only human figures, but also what Tim Ingold calls «nonhuman persons», including personal possessions, landforms, and animals, possess consciousness and interiority. Among wayang’s diverse story sources, the Ramayana stands out for its animistic qualities. Episodes depict interactions between humans, ogres, monkeys, deities, and other nonhuman persons, activating the potential of the medium for representing transformation and theatrically mining the suspension of natural laws. This essay, based on ongoing research into the wayang collection of Yale University Art Gallery, examines how the characters of the Ramayana reflect shifting theatrical styles and animistic beliefs. Analysis of these historical puppets is followed by an exploration of an experimental 2023 Ramayana production originated at the University of Con-necticut hybridizing wayang with the tholpavakoothu shadow puppet tradition of Kerala, India, in which the epic is retold from the perspective of the trees and wood inhabiting it.